2018
DOI: 10.1155/2018/6023460
|View full text |Cite
|
Sign up to set email alerts
|

Ag-Introduced Antibacterial Ability and Corrosion Resistance for Bio-Mg Alloys

Abstract: Bone implants are expected to possess antibacterial ability and favorable biodegradability. Ag possesses broad-spectrum antibacterial effects through destroying the respiration and substance transport of bacteria. In this study, Ag was introduced into Mg-3Zn-0.5Zr (ZK30) via selective laser melting technology. Results showed that ZK30-Ag exhibited a strong and stable antibacterial activity against the bacterium Escherichia coli. Moreover, the degradation resistance was enhanced due to the comprehensive effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Gao et al [10] showed that alloying magnesium with a small amount of Sr and Ga (up to 0.1 wt.%) effectively suppresses the activity of Gram-positive and Gram-negative bacteria (Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli), mainly due to the release of Ga 3+ ions. Magnesium alloyed with silver also shows similar properties [11][12][13][14].…”
Section: Introductionmentioning
confidence: 86%
“…Gao et al [10] showed that alloying magnesium with a small amount of Sr and Ga (up to 0.1 wt.%) effectively suppresses the activity of Gram-positive and Gram-negative bacteria (Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli), mainly due to the release of Ga 3+ ions. Magnesium alloyed with silver also shows similar properties [11][12][13][14].…”
Section: Introductionmentioning
confidence: 86%
“…With the increasing attention to the antibacterial properties of alloys, the antimicrobial performance of some developed Mg-Zn alloys started to be explored ( Zhang et al, 2020 ). At the same time, several novel Mg-Zn alloys with antibacterial alloying elements emerge ( Shuai et al, 2018a ; Feng et al, 2018 ). Zhang et al evaluated the antibacterial performance of alloy pins made out of Mg-2Zn-0.5Ca (named ZC21) alloy and Mg-4Zn-1Sr (named ZSr41) alloy with excellent degradable properties and biocompatibility in vitro .…”
Section: Research Progress Of Mg- Zn- and Fe-based Alloy Orthopedic I...mentioning
confidence: 99%
“…Excellent antibacterial performance is also shown in Zn. With this in mind, coupled with the antibacterial performance of zircon (Zr), both Mg-3Zn-0.5Zr (ZK30) ( Shuai et al, 2018a ) and Mg-6Zn-0.5Zr (ZK60) alloys ( Shuai et al, 2018b ) have been confirmed to have a certain antibacterial ability. Similarly, Qin et al evaluated the antibacterial potency of Mg-Nd-Zn-Zr alloy (named JDBM) that had been developed before.…”
Section: Research Progress Of Mg- Zn- and Fe-based Alloy Orthopedic I...mentioning
confidence: 99%
“…These alloying elements could significantly affect the attachment of bacteria and biofilm development and play an important role in the adhesion and corrosion process of materials in MIC environments [22]. Recent studies have shown the effect of several alloys on the adhesion of bacteria [14,[23][24][25][26][27][28][29][30][31][32][33]. Nickel has been reported to enhance bacterial attachment on stainless steel surfaces as it increases the number of bacteria and colonies on the surfaces of materials in both aerobic and anaerobic environments [14,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, molybdenum and ruthenium were shown to reduce bacterial attachment [26] even at low concentrations in the stainless steel alloys. Other antibacterial alloys such as copper and silver have also been investigated [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%